MENYUARAKAN HAK TANPA SEKAT: STUDI GERAKAN SOSIAL PETANI DI YOGYAKARTA - Izudin, Ahmad (JSW (Jurnal Sosiologi Walisongo), 2019)
Indonesia as an agrarian country is impressed by the fragile and exploitation. It causes the strengthening of three interactions; there is demography?s change, production to market, and the growing of the state. Based on the analysis, this article is explored the change of peasant expression on struggle of process movement. This paper is writing to known the change of political attitude by peasant which was approach Scott's theory on ?Social-Economic Morality?. This article is collected to take the qualitative method process with a case study approach. The data is aggregated with the interview and observation method. This result of research, that compromise is a technique to conduct of social movement by the peasant. This condition didn?t a reason to avoid a consequence of the state and there is exploitation and hegemonic inclined. Part of the ways is peasant confronting political attitude to facing of capitalism expansion. Consolidation organizing, protest of peasant right, and capacity improving trough empowerment are the consequence of peasant social movement. Three steps are the methods to opposite conflict escalation.